A baseline sarcopenia index based on creatinine/cystatin C for the prediction of stroke recurrence and mortality in older survivors of first ischemic strokes - Hou, Lisha; Chen, Xiaoyan; Zhu, Cairong (Frontiers in Public Health, 2023)
Objective: Elderly individuals have a higher risk of stroke recurrence, leading to high mortality and disability rates, which, in turn, hinders the achievement of healthy aging. This study aimed to assess the utility of a baseline sarcopenia index (SI) based on serum creatinine (Cr)/cystatin C (CysC) as a prognostic marker for the risk of stroke recurrence and mortality in first-ever ischemic stroke older survivors (ISOS).Materials and Methods: Data were obtained from an ischemic stroke cohort study.The baseline information was collected from medical records and face-to-face interviews with patients admitted between January 2010 and June 2016. Follow-up information was obtained from telephone interviews every three months to determine stroke recurrence and survival status. The SI was calculated from the Cr and CysC values in the medical records as Cr/CysC×100. Using the first quantile of the SI as the cut-off value, the study participants were divided into the low muscle-mass group (low SI) and the high muscle-mass group (high SI). Cox regression analysis was used to assess the association between SI and recurrence and mortality.Results: A total of 415 first-ever ISOS were enrolled, including 242 (58.31%) male and 173 (41.69%) female participants. In the high-SI group, the relapse and mortality rates were lower than those in the low-SI group (relapse: 20.58% vs. 30.77%; mortality:13.5% vs. 29.81%). After adjusting for confounding factors, the high-SI group was found to have a lower risk of relapse and mortality than the low-SI group (relapse: HR = 0.571; mortality: HR=0.294).The SI was predictive of the long-term prognosis of IS recurrence and mortality in first-ever ISOS. After discharge, in addition to conventional medication, it is recommended that patients with low SI values actively receive treatment for sarcopenia to reduce the risk of stroke recurrence and mortality and promote healthy aging.